CHARACTERISTICS AND POTENTIAL OF MICROPLASTIC DEGRADING BACTERIA FROM LOCAL MICROORGANISMS OF LERI ARUK FROM BANGKA BELITUNG - Desi, Desi; Syafiqo, Syafira Auliani; Olieviani, Marisa; Sari, Maya; Swandi, Monica Kharisma (Universitas Medan Area, 2025)
One of the efforts to reduce the impact of microplastic pollution is through local microorganisms (MOL). Practical and applicable MOL can be obtained from local materials such as leri aruk Bangka Belitung. This study aims to test the characteristics of various MOL formulations from leri aruk typical of Bangka Belitung as candidates for microplastic degradation agents and to characterize the bacteria. This study was conducted in several stages, namely sampling, making various MOL formulations, testing MOL based on physical, chemical and biological properties, isolation and characterization of microplastic degrading bacteria and testing the ability of bacteria to degrade microplastics. The results of the study obtained the best formulation results based on physical, chemical and biological properties, namely in formulation 2. The isolation results obtained 4 isolates that have the potential to degrade microplastics, namely isolates B13, B18, B19 and B20.Morphological and biochemical characterization of bacteria showed that isolates B13 and B19 were LactoBacillus, isolate B18 was Bacillus and isolate B20 was Escherichia. The consortium of 4 isolates can degrade microplastics by 7.14% for 1 week on LDPE plastic.